FAKTOR INTERNALDAN EKSTERNAL YANG BERPENGARUH TERHADAP KEBIJAKAN HUTANG DAN NILAI PERUSAHAAN (Studi Empiris pada Perusahaan BUMN Non Bank Yang Go-Public di Bursa Efek Indonesia) - Rinaldi Yonnia Firmansyah; Made Sudarma; Yeney Widia P (BALANCE: Economic, Business, Management and Accounting Journal, 2016)
ABSTRACT                  The purposed of research is analyzing the effect of internal factors and external factors to debt policy and to examine the effect of debt policy to corporate values. This research used the State-Owned Enterprises non bank which is listed in Indonesia stock exchange started the year 2007-2014 with total 10 Companies.Selection sample based on purposive sampling method with the purpose to get sample according to research aim. Based on the certain criteria which are assigned, so we get data pooling with analyze units 80. the analytical technique was multiple regressions.The research results show that external factors which are proxied by inflation rates, gross domestic bruto, interest rate, foreign exchange rate and crude oil prices has significant effect to debt policy. However, Internal factors which are proxied by profitability, corporate size, corporate growth and external factors which is proxied by composite stocks price index has no effect to debt policy. This research has also proved the debt policy has significant to corporate values. State-Owned Enterprises in taking policy on debt is influenced by external factors. The decision to use debt as source of funding will increase corporate value, its appropriate with trade off theory.Keywords : trade off theory, internal factors, external factors, debt policy and corporate values.Correspondence to : Inalak06@gmail.com